The Characteristics of Herbal Tea Combination Between Butterfly Flower with Mint and Pandan Leaf on Drying Duration Variation - Suryani, Titik; Rahmasari, Ria Anisa; Nisa, Riza Ainun (Universitas Muhammadiyah Surakarta, 2023)
Herbal tea is a functional bevarage made from leaf or flower. Butterfly flowers contain flavonoids, anthocyanins and flavonol glycosides. Mint leaf contain 1-2% essential oil and 80-90% menthol. Pandan leaf contain 10% essential oil, aromatic compounds 2-acetyl-1 pyrroline, flavonoids. The purpose of this study was to determine the characteristics (antioxidant activity and organoleptic quality) of herbal tea combination between butterfly flowers with mint leaf and pandan leaf on drying duration variations. This research method was an experiment with Completely Randomized Design (CRD), two factors. Factor I: combination of flowers butterfly : mint leaf (6 g : 2 g) and combination of butterfly : pandan leaf (6 g : 2 g). Factor II : drying duration of 90 minutes and 120 minutes The results showed that the highest antioxidant activity was K1L1 treatment (combination of butterfly flower: mint leaf with drying duration of 90 minutes) that was 83.147%. The best organoleptic quality of herbal tea in K1L1 treatment ( combination of butterfly flowers: mint leaf with drying duration of 90 minutes), dark blue color, mint aromatic, not bitter taste, fresh and quite like.